Comparison of endothelial cell loss and complications between phacoemulsification and manual small incision cataract surgery (SICS) in uveitic cataract - Bhargava, Rahul; Sharma, Shiv Kumar; Chandra, Mini; Kumar, Prachi; Arora, Yogesh (Nepalese Journal of Ophthalmology, 2016)
Introduction: Endothelial cell loss and complications after cataract surgery may be higher when cataract is complicated by uveitis. Objective: To compare endothelial cell damage and complication rates after phacoemulsification and manual small incision cataract surgery (SICS) in patients with uveitis. Materials and methods: Patients with uveitic cataract were randomly allocated for phacoemulsification (n=75) or manual SICS (n=80) in a double blind prospective study. In the bag implantation of a hydrophobic acrylic intraocular lens was aimed in all cases. Patients with follow up of less than six months were excluded. Main outcome measures were alteration in endothelial cell counts (ECC) and morphology, improvement in vision and complication rates. ECC was measured preoperatively and at 1 week, 3 months and six months, postoperatively. Results: Six patients were lost to follow up and another three due inability to implant IOL. There were no significant difference in endothelial cell counts (P= 0.032), the variance of endothelial cell size (CV) and percentage of hexagonal cells between both the groups at six months (Mann-Whitney test, P=0.283). Endothelial cell density was significantly less in the group in which vitrectomy and/or pupil dilatation procedures were performed (2290±31.5 cells/mm2) versus (2385±50.3 cells/mm2), respectively (t test, P<0.001). Incidence of postoperative complications that were observed like persistent uveitis (P=0.591), macular edema (P=0.671) and PCO (P=0.678) and visual outcome (P=0.974) were comparable between the two groups. Conclusions: Manual SICS and phacoemulsification do not differ significantly in endothelial cell loss and complication rates in uveitic eyes. However, increased anterior chamber manoeuvring due to additional procedures may lead to significantly higher endothelial cell loss.